Increased fecal ethanol and enriched ethanol-producing gut bacteria Limosilactobacillus fermentum, Enterocloster bolteae, Mediterraneibacter gnavus and Streptococcus mutans in nonalcoholic steatohepatitis - Mbaye, Babacar; Magdy Wasfy, Reham; Borentain, Patrick; Tidjani Alou, Maryam; Mottola, Giovanna; Bossi, Vincent; Caputo, Aurelia; Gerolami, Rene; Million, Matthieu (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Non-alcoholic steatohepatitis (NASH) has become a major public health issue as one of the leading causes of liver disease and transplantation worldwide. The instrumental role of the gut microbiota is emerging but still under investigation. Endogenous ethanol (EtOH) production by gut bacteria and yeasts is an emerging putative mechanism. Microbial metagenomics and culture studies targeting enterobacteria or yeasts have been reported, but no culturomics studies have been conducted so far.Aim: To assess fecal EtOH and other biochemical parameters, characterize NASH-associated dysbiosis and identify EtOH-producing gut microbes associated with the disease, fecal samples from 41 NASH patients and 24 controls were analyzed. High-performance liquid chromatography (HPLC) was used for EtOH, glucose, total proteins, triglyceride and total cholesterol. Viable bacteria were assessed with microbial culturomics. Microbial genetic material was assessed using 16S metagenomics targeting the hypervariable V3V4 region.: Fecal EtOH and glucose was elevated in the stools of NASH patients (p < 0.05) but not triglyceride, total cholesterol or proteins. In culturomics, EtOH-producing Enterocloster bolteae and Limosilactobacillus fermentum were enriched in NASH. V3V4 16S rRNA amplicon sequencing confirmed the enrichment in EtOH-producing bacteria including L. fermentum, Mediterraneibacter gnavus and Streptococcus mutans, species previously associated with NASH and other dysbiosis-associated diseases. Strikingly, E. bolteae was identified only by culturomics. The well-known Lacticaseibacillus casei was identified in controls but never isolated in patients with NASH (p < 0.05). Conclusions: Elevated fecal EtOH and glucose is a feature of NASH. Several different EtOH-producing gut bacteria may play an instrumental role in the disease. Culturomics and metagenomics, two complementary methods, will be critical to identify EtOH-producing bacteria for future diagnostic markers and therapeutic targets for NASH. Suppression of EtOH-producing gut microbes and L. casei administration are options to be tested in NASH treatment.